2012
DOI: 10.1155/2012/606285
|View full text |Cite
|
Sign up to set email alerts
|

Decision Making Cognition in Primary Progressive Aphasia

Abstract: Abstract. We sought to investigate the decision making profile of Primary Progressive Aphasia (PPA) by assessing patients diagnosed with this disease (n = 10), patients diagnosed with behavioral variant frontotemporal dementia (bvFTD, n = 35), and matched controls (n = 14) using the Iowa Gambling Task, a widely used test that mimics real-life decision making. Participants were also evaluated with a complete neuropsychological battery. Patients with PPA were unable to adopt an advantageous strategy on the IGT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…The increased impulsivity observed in bvFTD aligns with previous studies reporting impulsive decision-making in this population ( Strenziok et al. , 2011 ; Gleichgerrcht et al. , 2012 ; Bertoux et al.…”
Section: Discussionsupporting
confidence: 90%
“…The increased impulsivity observed in bvFTD aligns with previous studies reporting impulsive decision-making in this population ( Strenziok et al. , 2011 ; Gleichgerrcht et al. , 2012 ; Bertoux et al.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, the lack of an experimental task in the neuropsychological examinations. Prior reports have shown that, on a task like the Iowa Gambling Task, the pattern of gambling in PPA is different from bv-FTD 25. The experimental task could have been useful to distinguish compulsion from gambling behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Naming, as assessed using traditional tasks, is most frequently impaired in bvFTD patients. The most frequently used task was the Boston Naming Test (BNT), with 12 studies revealing impairments (Ash et al, 2016;Banks & Weintraub, 2008;Couto et al, 2013;De Winter et al, 2016b;Fernandez-Duque & Black, 2007;Lin et al, 2016;Peelle et al, 2008;Russo et al, 2014;Tan et al, 2015;Torralva et al, 2007;Whitwell et al, 2009;Wicklund et al, 2007) and six reporting preserved abilities (Chan et al, 2015;Gleichgerrcht et al, 2012;Kamminga et al, 2014;McKinnon et al, 2008;Rankin et al, 2007;Scherling et al, 2014).…”
Section: Word Retrievalmentioning
confidence: 99%